Cocculus hirsutus-Derived Phytopharmaceutical Drug Has Potent Anti-dengue Activity - Shukla, Rahul; Rajpoot, Ravi Kant; Poddar, Ankur; Ahuja, Richa; Beesetti, Hemalatha; Shanmugam, Rajgokul K.; Chaturvedi, Shivam; Nayyar, Kaushal; Singh, Deepika; Singamaneni, Venugopal; Gupta, Prasoon; Gupta, Ajai Prakash; et al. (Frontiers in Microbiology, 2021)
Dengue is a serious public health concern worldwide, with 3 billion people at risk of contracting dengue virus (DENV) infections, with some suffering severe consequences of disease and leading to death. Currently, there is no broad use vaccine or drug available for the prevention or treatment of dengue, which leaves only anti-mosquito strategies to combat the dengue menace. The present study is an extension of our earlier study aimed at determining the in vitro and in vivo protective effects of a plant derived phytopharmaceutical drug for the treatment of dengue. In our previous report, we had identified methanolic extract of aerial parts of Cissampelos pareira to exhibit in vitro and in vivo anti-dengue activity against all the four DENV serotypes. The dried aerial parts of C. pareira supplied by local vendors were often found to be mixed with aerial parts of another plant of the same Menispermaceae family, Cocculus hirsutus, which shares common homology with C. pareira. In the current study, we have found C. hirsutus to have more potent anti-dengue activity as compared to C. pareira. The stem part of C. hirsutus was found to be more potent ( 25 times) than the aerial part (Stem and leaf) irrespective of the extraction solvent used viz., denatured spirit, hydro-alcohol (50:50) and aqueous. Moreover, anti-dengue activity of stem extract in all the solvents was comparable. Hence, aqueous extract of stem of C. hirsutus (AQCH) was selected due to greater regulatory compliance. Five chemical markers viz. Sinococuline, 20-hydroxyecdysone, Makisterone-A, Magnoflorine and Coniferyl alcohol, were identified in fingerprinting analysis. In a test of primary dengue infection in the AG129 mice model, AQCH extract at 25 mg/kg body weight exhibited protection when administered QID and TID. The AQCH was also protective in the secondary DENV infected AG129 mice model at 25 mg/kg/dose when administered QID and TID. Additionally, the AQCH extract reduced serum viremia and small intestinal pathologies viz. viral load, pro-inflammatory cytokines, and vascular leakage. Based on these findings, we have undertaken the potential pre-clinical development of C. hirsutus-based phytopharmaceutical drug which could be studied further for its clinical development for treating the dengue.